Examining University Students' Business English Writing Performance: Frequent Errors and Pitfalls - ISMA, Adi; PUTRI, Andi Mega Januarti; SARDI, Ahmed (Research and Innovation in Applied Linguistics, 2024)
This study aims to identify the common writing errors made by college students in business English writing and investigate the contributing factors. The study employed a mixed-method approach to comprehensively analyze writing errors in the business English context. The research population comprised college students enrolled in Writing for Business Communication courses at Universitas Sulawesi Barat, with a sample of 100 students majoring in English education. The findings highlighted content errors, organization challenges, vocabulary issues, language use discrepancies, and mechanics errors in their writing. The most common errors encompassed grammatical errors in language use (48%), errors in conveying business messages in content (45%), and document structural errors in organization (38%). Moreover, the study identified several significant factors contributing to these writing errors, including a lack of practice, a limited understanding of business concepts, resource limitations, inadequate feedback, and time constraints. This study underscores the importance of addressing these specific writing challenges in business English education, offering insights for educators to develop targeted strategies and materials. It also contributes to the broader field by highlighting the unique errors within business English writing and emphasizing the need for specialized instruction. Ultimately, this research informs both pedagogical approaches and students' preparation for future careers in the globalized business environment.